Mitos del cine - Hitchcock, Alfred 1899-1980; Hayward, Susan 1917-1975; Bendix, William; Ondra, Anny, 1902-1987; Julian, Rupert, 1889-1943; Santell, Alfred, 1895-1981; Longden, John; Philbin, Marie; Chaney, Lon (Círculo Media Direct, 2009)
Una bella ejecutiva de una revista es acusada de asesinar a su antiguo novio (Pasión que redime)